1971
DOI: 10.2135/cropsci1971.0011183x001100010006x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gibberellic Acid on the Winter Growth of Varieties of Tall Fescue (Festuca arundinacea Schreb.)1

Abstract: The winter growth of varieties of tall rescue (Festuca arundinacea Schreb.) that had originated from the Mediterranean region (‘Oregon 1000’ and ‘Tunisian’)and northern Europe (‘Alta’) were studied outdoors in the Mediterranean climate of western Oregon, and in controlled environment chambers.Cubes of sod taken during the winter months from swards of Alta and Tunisian showed that Alta had a greater density of tillers and buds, and based on etiolated regrowth, a higher level of reserves. Monthly sowing of seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There has been a resurgence of interest in agronomic use of GA for pasture production, following substantial reductions in the price of isolating, and now synthesizing, this naturally occurring compound, which is one of a family of biologically active higher‐plant phytohormones identified originally in the fungal rice pathogen Gibberella fujikuroi (Kurosawa, ; Tudzynski et al ., ). Early studies in the 1950s and 1960s showed stimulation of harvestable yield in pasture grasses was possible, but was predominantly evident early in the growing season (Scurfield and Biddiscombe, ; Biddiscombe et al ., ; Arnold et al ., ; Blacklow and McGuire, ), with much reduced effects in enhancing growth in summer and until early autumn. This has been confirmed more recently, and particularly in cool‐temperate pastures, in extensive reviews by Matthew et al .…”
Section: Discussionmentioning
confidence: 99%
“…There has been a resurgence of interest in agronomic use of GA for pasture production, following substantial reductions in the price of isolating, and now synthesizing, this naturally occurring compound, which is one of a family of biologically active higher‐plant phytohormones identified originally in the fungal rice pathogen Gibberella fujikuroi (Kurosawa, ; Tudzynski et al ., ). Early studies in the 1950s and 1960s showed stimulation of harvestable yield in pasture grasses was possible, but was predominantly evident early in the growing season (Scurfield and Biddiscombe, ; Biddiscombe et al ., ; Arnold et al ., ; Blacklow and McGuire, ), with much reduced effects in enhancing growth in summer and until early autumn. This has been confirmed more recently, and particularly in cool‐temperate pastures, in extensive reviews by Matthew et al .…”
Section: Discussionmentioning
confidence: 99%
“…39 Beresford 1970), Canberra (Schiller & Lazenby 1975), and Hamilton (Reed 1985) have clearly demonstrated that the autumn and winter yields of tall fescue can be greatly improved using Mediterranean ecotypes. Not having to withstand harsh winter conditions, such types often partition more photosynthate to the foliage (Robson & Jewiss 1968;Blacklow & McGuire 1971). In addition to making greater growth in winter, the herbage of such types may contain as much as 23% more soluble carbohydrate, particularly fructans (fructosans), than that in the commercial winterdormant type of cultivar such as Alta (Blacklow & McGuire 1971).…”
Section: Tall Fescuementioning
confidence: 99%
“…Not having to withstand harsh winter conditions, such types often partition more photosynthate to the foliage (Robson & Jewiss 1968;Blacklow & McGuire 1971). In addition to making greater growth in winter, the herbage of such types may contain as much as 23% more soluble carbohydrate, particularly fructans (fructosans), than that in the commercial winterdormant type of cultivar such as Alta (Blacklow & McGuire 1971). The evolution of fructan-rich grasses appears to have been favoured by dry environments (Hendry 1993).…”
Section: Tall Fescuementioning
confidence: 99%
“…This is an interesting application, given that the indiscriminate application of GAs or GA inhibitors in the field causes secondary unwanted effects in all kinds of cultivated plants. For instance, it has been described that GA application causes a reduction in chlorophyll (Williams and Arnold, 1964), a decrease in the biomass of aerial tissues (Blacklow and McGuire, 1971), or a tendency to flower feminization in male corn flowers (Nickerson, 1960). Similarly, application of GA inhibitors causes severe alterations in the flowering time of certain species, difficult to reconcile with the desired compactness of ornamental plants (Rademacher, 1995).…”
Section: Biotechnological Implications Of Della Evolutionary Studiesmentioning
confidence: 99%